2015
DOI: 10.5539/ijbm.v10n2p158
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Technology Acceptance Model for Understanding the ICT Adoption Behavior of Rural Young Entrepreneurs

Abstract: Information and communication technologies (ICTs) open up new opportunities for rural young entrepreneurs to enhance their businesses. However, the challenges of adopting and using ICTs obstruct these businesses from growing into drivers for rural-economic development and job creation. The purpose of this paper is to seek to validate the technology acceptance model (TAM), which measures the volitional aspect of the ICT adoption behavior of young entrepreneurs in a rural community. In order to test the model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
2
18
0
2
Order By: Relevance
“…For instance, Standard Operation Procedures (SOPs) must be closely adhered to manage and align their business operating efficiently. The finding is in line with previous research that proper use of ICT will ensure the business success (Kurnia et al, 2015;Turban et al, 2008;Chen, 2013;Ong et al,2020;Zaremohzzabieh et al, 2015). ICT may provide a wide range of opportunities for women entrepreneurs' business development and act as a driving force to boost their business venture internationally.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, Standard Operation Procedures (SOPs) must be closely adhered to manage and align their business operating efficiently. The finding is in line with previous research that proper use of ICT will ensure the business success (Kurnia et al, 2015;Turban et al, 2008;Chen, 2013;Ong et al,2020;Zaremohzzabieh et al, 2015). ICT may provide a wide range of opportunities for women entrepreneurs' business development and act as a driving force to boost their business venture internationally.…”
Section: Resultssupporting
confidence: 90%
“…electronic commerce (Kurnia et al, 2015;Turban et al, 2008) that involves buying and selling process. Few studies show a positive effect of ICT on business performance while few shown its negativity (Zaremohzzabieh et al, 2015). ICT is on fame worldwide today that includes broadband, mobile and Internet, providing women entrepreneurs with the opportunity to do their business from anywhere and anytime.…”
Section: Ict and Business Performancementioning
confidence: 99%
“…This finding endorses that of Ahmed and Panda (2013) who show that 100% of the respondents in their study agreed and felt that electronic resources are useful to their work. Zaremohzzabieh et al (2015) reaffirm that several studies (e.g., Davis & Venkatesh, 2004;Kim, Mannino, & Nieschwietz, 2009;Loo, Yeow, & Chong, 2009;Sentosa & Mat, 2012;Teo & Noyes, 2011;Wang & Wang, 2010) reveal that PU effectively justified the intention to use an IT system. In an earlier similar study, Teo and Schaik (2009) admit that PU variables explain about 69% of the variance in attitude towards computer use among pre-service teachers.…”
Section: Discussion Of Findingssupporting
confidence: 56%
“…The aspects comprise positive perceptions that refer to factors that lead to their use and negative perceptions that refer to elements that discourage their usage (Silviyanti & Yusuf, 2015). The Technology Acceptance Model (TAM) was used in several previous studies on technology adoption aimed at person's acceptance of technology (Alshare et al, 2009;Baker-Eveleth et al, 2006;Davis et al, 1989;Davis & Wong, 2007;Emad et al, 2016;Goeke & Faley, 2007;Ha & Stoel, 2009;Kim & Bonk, 2006;Lin, 2008;Lin & Chou, 2009;Zaremohzzabieh et al, 2015). The Technology Acceptance Model (TAM) suggested that persons' states of mind towards another technology depend on the two key elements: Perceived Usefulness (PU) and Perceived Ease of Use (PEoU).…”
Section: The Importance Of Ict In Educationmentioning
confidence: 99%